Pemetaan Sarana dan Prasarana untuk Menunjang Pendidikan di Pascasarjana Universitas Jambi - Syarifuddin, Hutwan; Hamidah, Afreni; Adriani, Adriani (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This study aims to determine the weight of facilities and infrastructure in supporting the teaching and learning process at the Postgraduate Program at the University of Jambi based on the Analytical Hierarchy Process (AHP) method. The results of the AHP analysis showed that the building rooms had a weight of 0.83 and an open yard of 0.17. Then for the open page, the largest weight was found on Accessibility with a weight of 0.31 while the building space the largest weight on Flexibility with a weight of 0.34. Then for open yard has the largest weight on Accessibility with a weight of 0.31 while the building rooms weighs the largest on Flexibility with a weight of 0.34. Alternative facilities and infrastructure needed show that the Lecture Room and Seminar Room have the largest weight of 0.76. The construction of facilities and infrastructure for education is very necessary, especially for a more flexible building rooms for lecture room activities and student seminars.